ANALYSIS OF MATHEMATICAL ABSTRACTION ABILITY OF GRADE VIII STUDENTS IN CARTESIAN COORDINATE MATERIAL - Pratidiana, Deni; Rifa'i, Rusdian; Priyani, Dewi (MaPan : Jurnal Matematika dan Pembelajaran, 2021)
Mathematics is one of the most important branches of science because mathematics is indispensable for everyday life and is the basis for other branches of science. Therefore, students' abstraction ability is very important. Each student has abstraction ability in solving problems in mathematics lessons in solving different problems according to the students' level of thinking ability and intelligence. Therefore, the purpose of this research is to describe the mathematical abstraction ability of grade VIII students in cartesian coordinate material at SMPN 1 Cikedal. The type of research is a qualitative descriptive approach. The research subjects are 6 students of grade VIII A. The research instruments used are test sheets and interview guidelines containing 14 questions. The results showed that all the research subjects had low mathematical abstraction skills, as none of the students met all the levels and indicators used in this study, namely the level of recognition, representation, and structural abstraction.